Relationship between soil apparent electrical conductivity and pH value of jawa series in oil palm plantation - I., Nur Aini; Mohd Husin, Ezrin; Wayayok, Aimrun (Elsevier, 2014)
Having the correct pH is crucial for the healthy plant growth as it will affect the amount of nutrient available to plants. This study was carried out to determine the soil pH value in oil palm plantation based on ECa parameter measured by the soil sensor. The soil samples were collected in oil palm plantation at three different depth; 0 - 15 cm, 15 - 30 cm and 30 - 45 cm and the soil ECa was measured by using ECa sensor in the plantation. The study showed that ECa parameter had significant negative correlation to soil pH and highly related to deep ECa at the depth of 15 - 30 cm with R2 = 0.484